Farm Labour Wages in Tobacco Farming From an Islamic Perspective in Pujut District, Central Lombok Regency - Jufri, Akhmad; Sahri, Sahri; Huzaini, Moh.; Ismiwati, Baiq (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze farm labourers' wages in tobacco farming from an Islamic economic perspective in Pujut District, Central Lombok Regency. The research study focuses on implementing work agreements, the amount of wages, and the provision of wages to farm labourers in tobacco farming. This study uses a qualitative approach with a descriptive research type. Data collection was carried out through observation and in-depth interviews. Informants were determined using the snowball sampling technique and descriptive data analysis. The study concludes that labour wages in rice farming in Pujut District, Central Lombok Regency, have been implemented following Islamic law, namely the existence of an unwritten work agreement (agreement), work implementation according to the agreement, wages are paid on time according to the agreement, and there is an attitude of mutual assistance (ta'awun), sincerity, mutual consent (antaradin) and mutual consent (willingness) between workers and farm owners. It is recommended that workers in rice farming and tobacco farmers remain trustworthy and honest in implementing wages according to Islamic law as part of carrying out worship